Market-Based Estimation of Default Probabilities and its Application to Financial Market Surveillance - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2006)
This paper reviews a number of different techniques for estimating default probabilities from the prices of publicly traded securities. These techniques are useful for assessing credit exposure, systemic risk, and stress testing financial systems. The choice of techniques was guided by their ease of implementation and their applicability to a wide cross-section of countries and markets. Simple one-period cases are studied to sharpen the reader's intuition, and the usefulness of each technique for enhancing financial surveillance is illustrated with real applications.